ANALISIS PENURUNAN PONDASI TIANG BOR PADA JEMBATAN DENGAN METODE ANALITIS DAN PEMODELAN NUMERIK - Yufika, Alivia Wulan; Dana, Dinan; Firmansyah, Yerry Kahaditu (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Borepile are a critical component of bridge structures because they ensure the safe transfer of loads to deeper soil layers. In the Dhoho Kediri-Tulungagung Airport Toll Road Project, point P6 is one of the locations requiring in-depth evaluation of the bearing capacity and settlement of the foundation due to variations in local soil conditions. This study aims to analyze the performance of the borepile foundation at this point through analytical and empirical approaches, as well as numerical modeling using PLAXIS 2D to more comprehensively examine the soil-structure response. The analysis results indicate that the foundation was capable of meeting the required bearing capacity and producing settlement within tolerable limits. Numerical modeling also reveals deformation patterns and stress distributions consistent with the soil characteristics and foundation geometry. This combination of calculation and simulation methods provides a more comprehensive vision of the behavior of the borepile foundation at point P6. Overall, this study confirms that the borepile foundation at point P6 is suitable for use and capable of providing stable performance in supporting the bridge structure. These study can serve as a reference in the planning and evaluation of foundations in other segments with similar geotechnical conditions.